Modelling the Interaction of Illuminations with a Sensor Matrix Used in Vision Systems - Justyna Waśniowska; Andrzej Sioma (Applied Sciences, 2023)
The article discusses a method of modelling the interaction of industrial illuminators with sensor arrays used in industrial vision systems cameras. The research used a model containing a light source and a sensor matrix. As part of the research, the average intensity of electromagnetic radiation in the visible range on the surface of the sensor matrix was measured, as well as its analysis and interpretation using a model of illuminators. The light source is described based on the measurement of an authentic industrial illuminator, for which a photometric solid was determined using a photogoniometer and spectral irradiance with a spectroradiometer. A theoretical model of the matrix was prepared, enabling the selection and control of the parameters of its work. As part of the conducted research, the impact of changing the lighting model parameters, such as the photometric solid, spectral irradiance, and number of rays, and the effect of changing the matrix parameters, such as the dimensions, number of pixels, on the irradiance measurement, were checked. The results of simulation tests are presented for selected sets of models of the light source and for the model of sensors’ matrix. The summary presents the impact of changes in parameters adopted for models on the simulation results.